EFEKTIFITAS PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) TERHADAP HASIL BELAJAR PADA MATA PELAJARAN FIKIH KELAS VIII DI MTsN 4 LIMA PULUH KOTA - Sri Wahyu Lillah; Supriadi; Charles; Alimir (KOLONI, 2022)
The background of the author raised the title of this research based on the results of observations of researchers with fiqh educators and with students at MTsN 4 Lima Puluh Kota, showing that student learning outcomes are not balanced and are classified as low. This is due to the large number of students who are not active in learning and educators are less creative in choosing good learning media and in accordance with the interests of students. Educators should be able to use a variety of media that are easily understood by students, one of which is by using LKPD in learning. Learning media with this LKPD can help students be more active and independent in the learning process so that their learning outcomes increase. This study uses a quantitative method with the type of Quasy Experiment Design by using tests. The population in this study were all eighth grade students at MTsN 4 Lima Puluh Kota. Sampling used normality and homogeneity tests and all samples were normally distributed and the data variance was homogeneous, so the researchers chose class VIII.3 as the control class and class VIII.4 as the experimental class because class VIII.3 obtained the highest average and class VIII.4 get the lowest average. Research data on student learning outcomes in fiqh subjects were obtained from test answers. Based on the results of the analysis and discussion of the research data, the hypothesis results obtained by t-test, tcount = 4.117 and ttable = 1.714, then tcount > ttable so that H0 is rejected. Based on these results it can be concluded that, "the learning outcomes of students who take part in learning using LKPD are better than students who take part in learning using other media".  Keywords: LKPD, Learning Outcomes, Fiqh